History, Memory and Fiction: What Boundaries? - Matos, Sérgio Campos (História da Historiografia: International Journal of Theory and History of Historiography, 2015)
20th century sociologists and historians established a clear distinction between history and memory. But in the last decades our attention has been called to what exists in common between these two fields that do not always coincide. In this article, I intend to problematize the complex relationship between history and memory: the critical demands of history writing and the register of the various memories (individual memory, collective memory), also equating the relationship between memory and -forgetfulness. And what about history? What distinguishes it from fiction? To what extent are memories permeable to imagination? We all fictionalize our past. Could we reduce the writing of history to a narrative dimension?